#TITLE_ALTERNATIVE# - DIWITA NISAEKTI (NIM : 15113071), WINDY
Bandung, one of the Metropolitan City that has high population growth. The presence of population growth not only affects the number of people residing in the area, but also on the needs of residence, food, and clothing that is required to be fulfilled. To achieve the necessities, the demand for the quantity of land will increase but the amount of available land remain constant, therefore the land price will increase. As the city with a rapid development, the price of land will also rise quickly, thus renewal of the Land Value Zone Map is needed. Therefore, it needs a method which can obtain an update effectively and efficiently on balancing the price of the land that keeps changing. The price of land will affect the Tax Object Sales Value (NJOP) set by the government. For the purpose of determining NJOP based on the parcelsÃ‚Â’ availability, the determination of NJOP is conducted based on Land Value Zone (ZNT), in the form of imaginary boundary which consists of blocks of land with relatively same price. Based on existing processes, ZNT map making is complex and takes a long time. Therefore, an alternative method is needed to make a faster ZNT map, one of them is interpolation method. In this research used Inverse Distance Weighted (IDW) interpolation with land price of Kelurahan Sukamaju, Kecamatan Cibeunying Kidul, Bandung, West Java, to get an approximation of the ZNT Map, and do analysis of ZNT map of interpolated results. IDW Interpolation is an interpolation method that applies the ratio of values that surround it, with a magnitude of weights that are inversely proportional to distance. The result obtained from this research is IDW interpolation method can be applied in making the ZNT map.